Membangun Karakter Kewirausahaan di Kalangan Pembudi Daya Biji Jenitri Desa Pengaringan dengan Mengembangkan Desain Aksesoris - Djakaria, Elliati; Ginting, Seriwati; Andreas, Isabella Isthipraya (Ideas Publishing, 2023)
The study was carried out in Pangaringan Village, which is a producer of Jenitri seeds that are shipped to China and India. The buyer sets both the price and the quality; Jenitri seeds that the buyer deems subpar are sold for extremely low prices. The purpose of this study is to expand on the health advantages of Jenitri seeds by creating accessories with a variety of styles and combining them with other locally available natural components. This study employed a participatory descriptive research design, wherein the research team creates possibilities for craftspeople to develop. The findings of the study demonstrate that other materials, including wood, stone, bone, and others, can be used to design Jenitri seeds. A distinct appearance is produced by the mix of materials with Jenitri seeds, including the accessory's color scheme. It takes constant passion and creativity to create this design in line with different societal advancements. As a result, this study highlights the value of strong moral character in Jenitri seed farmers, who are also artisans. It is implied that growers have other revenue streams, such as sales of accessories and exports of raw materials (Jenitri seeds that haven't been turned into accessories). In addition to attending seminars and exhibits, growers make the most of the interim period between planting and harvesting by putting different types of janitri seed accessories into practice.